Illustrated catalogue of type specimens of insects (Hexapoda) at Coleção Entomológica “Prof. J.M.F.Camargo” (RPSP), Universidade de São Paulo, Brazil - Almeida, Eduardo A. B.; Costa, Anne M.; Filho, José Amilcar Tavares; Zichinelli, Marcela M. P.; Quinteiro, Fábio B. (Zootaxa, 2020)
The present catalogue lists the insect types (Hexapoda) deposited at Coleção Entomológica “Prof. J.M.F.Camargo” (RPSP), Universidade de São Paulo, Ribeirão Preto, Brazil. This collection is known as one of the most significant depositories of stingless bees (Hymenoptera: Apidae: Meliponini) for the Brazilian and Neotropical faunas, largely because of the legacy of Professor João Franco Maria de Camargo (in memoriam) and co-workers. The Meliponini constitute the most emblematic portion of the collection, comprising 3,335 type-specimens (66 holotypes, 3,254 paratypes, and 15 paralectotypes), which represent 132 species-names. In addition to stingless bees, 495 type specimens of other Hymenoptera (23 holotypes and 472 paratypes) are deposited at RPSP representing 71 hymenopteran species-names: Agaonidae (16 names), Andrenidae (3 names), non-Meliponini Apidae (21 names), Chrysididae (2 names), Halictidae (16 names), Colletidae (5 names), Megachilidae (5 names), Melittidae (1 name), Pteromalidae (1 name), and Vespidae (1 name); the only other insect order currently represented by types at RPSP is Diptera (Drosophilidae: 2 names). Altogether, there currently are 3,832 type-specimens deposited at RPSP. Label data and additional information from the RPSP registers, literature sources, and taxonomic remarks are given, including photographs of name bearing types and representatives of other type specimens of the species herein considered.